PENERAPAN KURIKULUM 2013 DALAM PEMBELAJARAN BAHASA ARAB DI MADRASAH IBTIDAIYAH - Mufidah, Nuril; Nadhifah, Naura; Kholis, Nur (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
This study aims to describe the process of learning Arabic using the 2013 curriculum and the effects given to students, teachers, and other school parties. This research was conducted on 5th-grade students of MI Al-Ihsan Banjarwungu, Sidoarjo, in the 2021/2022 academic year. This study uses a qualitative design with a case study method. The instruments used in this study were observations of the Arabic learning process based on the 2013 curriculum, interviews with Arabic teachers, as well as an analysis of documentation from the notes and report cards of 5th graders, well as notes on students' interests and criticisms of learning Arabic using the 2013 curriculum. The results showed that implementing the 2013 curriculum at MI Al-Ihsan Banjarwungu, Sidoarjo indicates that teachers have many innovations in the Arabic language learning process, starting from changes in RPP writing to the learning process. One form of creation is the application of interesting new methods in the learning process, such as singing and guessing words, as well as using media tools and pictures in the Arabic learning process. The results also show influences on students and teachers in the 2013 curriculum-based Arabic learning process. Several respondents from 5th-grade students of MI Al-Ihsan stated that interest in learning Arabic increased during the 2013 curriculum-based learning process. Arabic teacher grade 5 MI Al-Ihsan said that learning Arabic based on the 2013 curriculum is more interesting to apply to students but has a complicated assessment process.